Joint Design of Transmission Rate and Control for Wireless Sensor Networked Control Systems - Jinna Li; Peng Zeng; Xuejun Zong; Meng Zheng; Xiaoling Zhang (Journal of Electrical and Computer Engineering)
This paper is concerned with transmission rate and control codesign of wireless sensor networked control systems (WSNCS) with time-varying delay. Jointly designing transmission rate and control is an attractive paradigm for WSNCS, since the control performance of WSNCS is highly sensitive to resource-constrained communication networks. The main idea of devised scheme is searching an optimal event-triggered transmission condition on the premise that wireless link capacity constraint is satisfied and stability of systems is guaranteed. The main aim of devised scheme is to greatly optimize control performance of WSNCS. First, two wireless network architectures characterized by multihop and star topology are put forward. Secondly, a model of WSNCS with event-triggered transmission mechanism is constructed. It is followed by stability analysis of WSNCS to obtain the asymptotical stability condition of systems. And then a search algorithm is presented for transmission rate and control codesign. Finally, numerical examples are given to illustrate the effectiveness of the proposed method.